Legal Analysis of Corporate Criminal Liability in Corruption Crimes (Study of Decision Number 16/Pid.Sus-Tpk/2022/Pn. Smg) - Rozi Juliantono; Gunarto Gunarto (UNISSULA Semarang, 2025)
Abstract. This research discusses corporate criminal liability in corruption offenses, focusing on Semarang District Court Decision Number 16/Pid.Sus-TPK/2022/PN Smg. The background of this research is based on the widespread practice of corruption, which is not only committed by individuals but also involves corporations as instruments to gain profit against the law. The main issues of this research include: (1) how corporate criminal liability is regulated in corruption offenses under positive law in Indonesia; (2) how corporate criminal liability is applied in Decision Number 16/Pid.Sus-TPK/2022/PN Semarang; and (3) what are the prospects for developing the application of corporate criminal liability in the future. The research method used is a normative legal approach with primary data in the form of laws and court decisions, and secondary data in the form of literature, journals, and legal doctrines. The research results show that the regulation of corporate criminal liability in Indonesia has a clear legal basis through the Anti-Corruption Law, Supreme Court Regulation No. 13 of 2016, and the new Criminal Code (Law No. 1 of 2023). In Semarang District Court Decision No. 16/Pid.Sus-TPK/2022, the judge affirmed that corporations can be held criminally liable under Article 20 of the Anti-Corruption Law, proved the elements of the crime through the identification theory and vicarious liability, and imposed a sentence of fines and restitution. The future outlook indicates that regulations are becoming increasingly stringent, but successful implementation still depends on legal harmonization, the capacity of law enforcement agencies, the compliance culture of the business world, and international cooperation. Thus, corporate criminal liability in corruption offenses serves not only as a repressive instrument for punishment but also as a preventive instrument to deter corruption, strengthen transparent and accountable corporate governance, and achieve substantive justice.